Estimation of Heavy Metal Concentrations in Solid Particles Residue Collected from Baghdad Street Dust - Althwainy, Muntaha. N.; Alsalman, Ibrahim. M .A; Mahdi, Jenan. H . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study have been conducted to estimated the  concentration levels of heavy metals  in samples  of solid particles residue which collected randomly from street dust that produced  with neglected municipality wastes  in Baghdad City. Samples were collecting from services and dwelling street in Elmashtal region in Resapha side and Albaya regions in Karkh side at Baghdad City, regions characterized with different activities, a qualities analysis for the compounds doing with the following tests: 1- By using soil sieves was fragmented and limited the particulates of dust especially the dangerous types which associated with dust compounds and air pollution. 2- Digesting and analyzing of samples have been done to limit the concentrations of heavy metals that were expected in mineral part and the dust.             The results revealed that there are 8 heavy elements  ( Cu, Zn, Pb, Fe, Mn, Co, Cr and Cd) with average  (60.718  ØŒ235.25   ØŒ 128.437 ØŒ805.812  ØŒ181 ØŒ11.437  ØŒ24.625ØŒ Ùˆ 2.05   ppm   ) for each element respectively.             From the results of present study we can conclude that the solid residues of street dust actively associate with the increase of the percentage of suspended dust loaded with heavy metals in Baghdad atmospheric air, and caused direct effects on population and Biosystem of the City, so we need to be more careful to apply the rules of the environmental manipulation from the wastes which the problem.